Guide to HTML, JavaScript and PHP for scientists and engineers - Brooks, David R. 1941-; SpringerLink (Online service). (London Springer, 2011)
HTML, JavaScript, and PHP are Web-based programming languages that can be used to solve computational problems in an online environment. This easy-to-read, informative guide/reference will enable readers to quickly develop a working knowledge of HTML, JavaScript and PHP a valuable skill for any scientist or engineer. Updating and expanding upon the author's previous Springer titles, An Introduction to HTML and JavaScript and An Introduction to PHP, the text emphasizes a hands-on approach to learning and makes extensive use of examples throughout the book. A detailed science, engineering, or mathematics background is not required to understand the material, making the book ideally suitable for self-study or an introductory course in programming. Topics and features: Describes the creation and use of HTML documents, including tables, forms, lists, frames, and cascading style sheets Presents fundamental concepts of client-side and server-side programming languages and their application to scientific and engineering calculations, using JavaScript and PHP Examines JavaScript and PHP implementation of arrays, built-in and user-defined methods and functions, math capabilities, and input processing with HTML forms With PHP, extends programming fundamentals to include reading and writing server-based files, command-line interfaces, and an introduction to GD graphics Appendices include lists of ASCII and HTML special characters, and a brief introduction to using a "pseudocode" approach to organizing solutions to computing problems Includes a Glossary and an extensive set of programming exercises This highly useful guidebook supplies all the tools necessary to begin programming in HTML, JavaScript and PHP for scientific and engineering applications. Its clear writing style, with a focus on the importance of learning by example, will appeal to both professionals and undergraduate students in any technical field. Dr. David R. Brooks is president and founder of the Institute for Earth Science Research and Education, Eagleville, PA, USA. He was formally a research professor at Drexel University, Philadelphia, PA, USA. He is the author of a number of successful Springer titles, including Problem Solving with Fortran 90 for Scientists and Engineers, and C Programming: The Essentials for Engineers and Scientists.
Introducing HTML and JavaScript -- HTML Document Basics -- HTML Tables, Forms, Lists, and Frames -- Fundamentals of the JavaScript Language -- Using Arrays in HTML/JavaScript -- JavaScript Functions -- Creating a Server-Side Environment with PHP -- Working with PHP -- PHP Arrays -- Summary of Selected PHP Language Elements -- Using PHP from a Command Line -- Using Graphics with PHP.
Electronic reproduction.
Keywords: Programming languages (Electronic computers) -- Handbooks, manuals, etc; HTML (Document markup language) -- Handbooks, manuals, etc; JavaScript (Computer program language) -- Handbooks, manuals, etc; PHP (Computer program language) -- Handbooks, manuals, etc; Electronic books